A contribui????o da log??stica reversa na gest??o de res??duos s??lidos : uma an??lise dos canais reversos de pneum??ticos - Goto, Andr?? Kenreo (2007)
The objective of this work is to analyze the contribution of the reverse logistics in the administration of solid residues for the adaptation of the companies to the Resolution 258/99, that treats of the correct disposition of the tires. The development of the research began with method of the exploratory research, seeking a better understanding of the reverse logistics, of the subjects related to the administration of the solid residues and of the profile of the section of tires, through the bibliographical and documental researches. For understanding of the administration of solid residues in the chain logistics of tires, the exploratory research was complemented by the qualitative and quantitative descriptive researches. The qualitative research was accomplished through interviews structured the leaders of the manufacturers' associations close to and of reformers of tires and with the representative of IBAMA. The quantitative descriptive research was accomplished through applied questionnaires to the reformers, to the resellers and the consumers of tires. In spite of the controversy around the import of used tires, Brazil reuses tires of other countries, contributing with the destination of residues of useless tires of developed countries. The research also showed that the participants of the reverse channels act in way differentiated in the stages of the administration of solid residues. The consumers contribute in the reduction of the consumption through the periodic maintenance of the vehicle and of the use of the tire to the end of the useful life, surpassing safety's limits, but still group the tires used home with risk of depositing at inadequate places. The resellers address the used tires left by the consumers for reform or recycling. The reformers reuse the tires used in the reform, substituting the consumed part, prolonging the life of the product and placing the country in the second place in the ranking of reform of tires in the world. The manufacturers and the importers created programs of collection of useless tires to destine to the recycling and the incineration for earnings of energy. The results appear although the reverse channels are not structured for manage the residues of tires and to reduce the environmental impact of the section.